2013
DOI: 10.1177/0192513x13513582
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Satisfaction and Communication Among Urban Minority HIV-Positive and HIV-Negative Mothers

Abstract: Family relationships influence children’s beliefs and behaviors. This work examined qualities associated with communication about alcohol among 176 mothers and the influence of this communication on daughters’ alcohol use. Path analyses by maternal HIV status indicated significant differences. Relationship satisfaction was associated with self-efficacy for both HIV-positive (β = 0.545, p < .001) and HIV-negative (β = 0.557, p < .001) mothers. Maternal self-efficacy was associated with communication for both HI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 76 publications
0
3
0
Order By: Relevance
“…Therefore, parents are encouraged to continue maintaining an open line of communication with their children, especially during adolescence, even if these discussions might not be specifically focused on risk taking or peer influence. For example, parent–child relationship satisfaction is instrumental in enhancing the effectiveness of parent–child communication (Cederbaum et al 2014; Ennett et al 2001). Therefore, although targeted parental communication and monitoring are vital, it is imperative that parents also spend quality time with their children, nurturing these relationships.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, parents are encouraged to continue maintaining an open line of communication with their children, especially during adolescence, even if these discussions might not be specifically focused on risk taking or peer influence. For example, parent–child relationship satisfaction is instrumental in enhancing the effectiveness of parent–child communication (Cederbaum et al 2014; Ennett et al 2001). Therefore, although targeted parental communication and monitoring are vital, it is imperative that parents also spend quality time with their children, nurturing these relationships.…”
Section: Discussionmentioning
confidence: 99%
“…The number of participants in Oita, Osaka, Miyagi, and Kagawa prefecture was 2,488 (52.1%), 1,329 (27.9%), 897 (18.8%), and 58 (1.2%), respectively. The median of the first assessment was 11 (interquartile range [9][10][11][12][13][14][15][16][17]. The number of women with consistently satisfied, improving, deteriorating, and consistently unsatisfied relationship with parents was 4,340 (91.0%), 129 (2.7%), 122 (2.6%), and 181 (3.8%), respectively.…”
Section: Resultsmentioning
confidence: 99%
“…In conjunction with childhood abused history, the association between the parent-daughter relationship and health problems has been also reported throughout the life course. In studies of adolescents, for example, poor parent-daughter relationship has been shown to be associated with eating disorder ( 12 ), risky sexual behavior ( 13 , 14 ), alcohol use ( 15 ), and suicide attempt ( 16 ). In a study of adults, women who continued to perceive lower levels of closeness with parents had higher risk of psychological distress in adulthood ( 17 ).…”
Section: Introductionmentioning
confidence: 99%